Synthesis of Self⁃Supported Pt@Ni(OH)2 Catalysts and Their Electrocatalytic Hydrogen Evolution Performance for Water Splitting - Kangsheng HUANG; Ning WANG; Mingrui GUO (Shiyou huagong gaodeng xuexiao xuebao, 2025)
The efficient production of hydrogen as a clean energy carrier relies on the performance optimization of electrocatalysts for the hydrogen evolution reaction (HER).Although platinum (Pt)⁃based catalysts exhibit exceptional HER activity,their high cost and stability issues can be mitigated through rational design of the support material.Nickel hydroxide (Ni(OH)₂) has emerged as a promising support due to its unique proton conductivity,interfacial modulation properties,and stabilizing effects on Pt. However,a systematic understanding of the structure–activity relationship between Ni(OH)₂ supports and Pt nanoparticles,as well as the impact of synthesis parameters on catalytic performance,remains lacking.This study focuses on the regulation of Ni(OH)₂ support phase evolution and Pt interfacial growth behavior by hydrothermal synthesis temperature.By analyzing the structure–performance relationship through the synthesis parameter–microstructure–catalytic performance correlation mechanism),the synergistic effects of temperature on the crystallinity of the support,Pt particle size distribution,and interfacial electronic structure were elucidated.Experimental results indicate that the Pt@Ni(OH)₂ catalyst synthesized at 100 ℃ exhibits outstanding HER activity in 1 mol/L KOH electrolyte,with overpotentials of only 5 mV at 10 mA/cm² and 62 mV at 100 mA/cm²,along with a Tafel slope of 70.0 mV/dec.After 50 hours of continuous operation,the electrode maintains nearly unchanged HER performance,demonstrating remarkable stability.